Ethnographies of development and globalization in the Philippines emergent socialities and the governing of precarity - Seki, Koki (Abigdon, Oxon Routledge, 2020)
"The contributors to this volume examine the actual workings and on-the-ground effects of contemporary political economic shifts in the Global South, and implications for reconfiguring social networks, conceptions and practices of governance, and burgeoning social movements. How do various groups in the Global South respond to and manage chronic states of insecurity and precarity concomitant with contemporary globalization processes? While drawing on diverse ethnographic viewpoints in the Philippines, the authors analyze the impact of these processes through the conceptual framework of "emergent sociality," a purported connectedness among individuals fostered through interactions, copresence, and conviviality within a community over a long duration. In so doing, the case studies in this volume suggest, illuminate, and debate insecurities that may be commonly shared among populations in the Philippines and throughout the Global South. This anthology will be of great interest to students and scholars of cultural anthropology, globalization and Philippines society"--
Post-authoritarian sociality and urban governmentality: a socialized housing project in metro Manila -- Neoliberalizing subaltern political socialities: community barricade and the diverse grassroots struggles for adequate housing in the Sitio San Roque slum -- Disaster, discipline, drugs and Duterte: emergence of new moral subjectivities in Post-Yolanda Leyte -- Learning to leave: Filipino families and the making of the global Filipino nurse -- Diasporic socialities and long-distance love stories: transnational volunteerism and making the ideal Filipino citizen -- Two dimensions of "the social": oppression and solidarity in tourism development of Boracay Island -- Rearraying available resources to secure livelihoods: continuities and change in livelihood strategies in a rural village in Ilocos, Philippines -- The role of kinship relations among Maranaos living in double-peripheries.
Includes bibliographical references and index.
Keywords: Globalization -- Social aspects -- Developing countries; Human security -- Social aspects -- Developing countries; Globalization -- Social aspects -- Philippines -- Case studies; Human security -- Social aspects -- Philippines -- Case studies; Developing countries -- Social conditions; Philippines -- Social conditions